2006
DOI: 10.1007/s11262-005-0030-z
|View full text |Cite
|
Sign up to set email alerts
|

The Intraleader AUG Nucleotide Sequence Context is Important for Equine Arteritis Virus Replication

Abstract: The 5(-terminal leader sequence of the equine arteritis virus (EAV) genome contains an open reading frame (ORF) with an AUG codon in a suboptimal context for initiation of protein synthesis. To investigate the significance of this intraleader ORF (ILO), an expression plasmid was generated carrying a DNA copy of the subgenomic mRNA7 behind a T7 promoter. Capped RNA transcribed from this construct was shown to direct, in an in vitro translation system, the synthesis of leader peptide as well as N protein. Site-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…It might be expected that in these cases, the uORF in the genome would be a regulator of not only translation but also virus replication and perhaps also virus-induced pathogenesis. A single AUG-initiated uORF is found in the genomes of arteriviruses (13,14,16) and most coronaviruses (17; this study), two families of animal positive-strand RNA viruses in the order Nidovirales (18). The role of the uORF in these viruses has undergone limited study.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…It might be expected that in these cases, the uORF in the genome would be a regulator of not only translation but also virus replication and perhaps also virus-induced pathogenesis. A single AUG-initiated uORF is found in the genomes of arteriviruses (13,14,16) and most coronaviruses (17; this study), two families of animal positive-strand RNA viruses in the order Nidovirales (18). The role of the uORF in these viruses has undergone limited study.…”
mentioning
confidence: 95%
“…In other cases, 5=-cap-dependent translation of the uORF enhances translation of the main ORF by various mechanisms (1,2,4,(7)(8)(9)(10)(11). Some plant (12) and animal (13)(14)(15) viruses that have a positive-strand (mRNA-like) genome which undergoes necessary 5=-cap-dependent translation prior to viral genome replication in the cytoplasm also have a (usually single) short uORF. It might be expected that in these cases, the uORF in the genome would be a regulator of not only translation but also virus replication and perhaps also virus-induced pathogenesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Looking to the Arteriviridae family, EAV has a highly conserved AUG within the leader (present in 94/95 available genome sequences), at genomic coordinates 14-16, predicted to permit expression of a 37-amino-acid leader peptide 118 . In vitro translation of the N transcript demonstrated that the uORF is translated, and found it down-regulated translation of the downstream N ORF 119 . Mutations which disrupted this AUG or altered its predicted initiation efficiency were detrimental to viral fitness and led to rapid reversion to the WT sequence 119 , although the uORF was not essential for virus viability 119,120 .…”
Section: Discussionmentioning
confidence: 99%
“…In horses the Kozak sequence is commonly found as an initiation signal for gene translation as in other vertebrates [ 21 ]. For equine arteritis virus suboptimal intraleader AUG and not an optimal Kozak sequence has been shown to be critical for virus replication [ 26 ].…”
Section: Discussionmentioning
confidence: 99%